Accounting, new public management and performance measurement: the Spanish versus the Anglo-Saxon experience. (1st January 2012) - Brusca, Isabel; Montesinos, Vicente
The aim of this paper is to show which reforms have been carried out in Spanish administrations to improve their management in terms of accounting, performance measurement and output-based budgeting, comparing them with the new public management paradigm of Anglo-Saxon countries. We try to analyse whether there has really been a reinvention of Spanish Government or only an attempt to improve or renovate the image of the government.